Pengaruh Self-Efficacy, Budaya Organisasi Dan Motivasi Kerja Terhadap Komitmen Organisasi [The Influence of Self-Efficacy, Organizational Culture, and Work Motivation toward Organizational Commitment] - Yulan Yulan; Innocentius Bernarto (DeReMa (Development Research of Management): Jurnal Manajemen, 2017)
The objectives of this study is to find out the following: 1) does self-efficacy have a positive influence on work motivation, 2) does organizational culture have a positive influence on work motivation, 3) does self-efficacy have a positive influence on organizational commitments, 4) does organizational culture have a positive influence on organizational commitments, and, 5) does work motivation have a positive influence on organizational commitments in a TMAP Foundation. The data collection in this study is done using a questionare given to all employee of the foundation. The number of the respondents was 30 people. The method used in this research was quantitative research by using the path analysis method. This study is using the PLS-SEM approach with the help of SmartPLS tools to evaluate the outer model and inner model. The finding of this study is that self-efficacy has positive effects on work motivation, organizational culture has positive effects on work motivation, self-efficacy has positive effects on organizational commitments, organizational culture has positive effects on organizational commitments, and working motivation has positive effects on organizational commitments. This study can provide input for the foundation to develop and empower their employees so they can become better. In addition, the results of this study can also help other non-profit organization foundations located specifically in remote areas.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk mengetahui: 1) apakah self-efficacy memiliki pengaruh positif terhadap motivasi kerja, 2) apakah budaya organisasi memiliki pengaruh positif terhadap motivasi kerja, 3) apakah self –efficacy memiliki pengaruh positif terhadap komitmen organisasi, 4) budaya organisasi memiliki pengaruh positif terhadap komitmen organisasi, 5) motivasi kerja memiliki pengaruh positif terhadap komitmen organisasi bagi karyawan Yayasan TMAP. Pengumpulan data dilakukan dengan penyebaran kuesioner kepada seluruh karyawan di Yayasan TMAP. Jumlah responden yang menjadi subjek penelitian adalah sebanyak 30 responden. Penelitian ini menggunakan pendekatan kuantitatif dengan metode analisis jalur (path analysis). Pendekatan PLS-SEM dengan bantuan program SmartPLS digunakan untuk mengevaluasi model pengukuran (outer model) dan model struktural (inner model). Hasil penelitian menunjukkan bahwa self-efficacy berpengaruh positif terhadap motivasi kerja, budaya organisasi berpengaruh positif terhadap motivasi kerja, self-efficacy berpengaruh positif terhadap komitmen organisasi, budaya organisasi berpengaruh positif terhadap komitmen organisasi, dan motivasi kerja berpengaruh positif terhadap komitmen organisasi. Kontribusi penelitian ini dapat memberikan masukan kepada manajemen yayasan untuk mengembangkan dan memberdayakan karyawan agar menjadi lebih baik sehingga dapat meningkatkan taraf hidup mereka. Selain itu, hasil penelitian ini juga dapat menjadi masukan bagi yayasan non profit lainnya terutama yang berada di daerah-daerah pedalaman.